The Necessity Defense and Climate Change: A Climate Change Litigant’s Guide - Rausch, Joseph (Columbia Journal of Environmental Law, 2019)
Civil disobedience is defined as “illegal public protest, [that is] non- violent in character.” Examples of such activity include “trespassing on government property, blocking access to buildings, or engaging in disorderly conduct.” Civil disobedience signifies disagreement with public policies that individuals feel are not being properly addressed through the normal political channels. The sense that they have no other political or legal recourse leads people to respond to the issue with protests. Not surprisingly, civil disobedience has been a popular avenue for climate change advocates. In fact, Kara Moss, an opinion writer for the Guardian, went so far as to claim that civil disobedience might be the only route left in the fight against climate change. Civil disobedience in the realm of climate change has been successful in stopping, or at least slowing down, particular projects. For example, the Keystone XL Pipeline, a pipeline that would transfer fuel from Canadian tar sands to the United States, has been a hotly debated political issue. One reason protests have erupted across the country to try and thwart the construction of the pipeline is the exacerbation this source of energy could have on climate change. Some activists even turned to civil disobedience in a last ditch effort to make their disagreement with the construction of the pipeline known. As a result, on November 6, 2015, President Barack Obama denied the pipeline an essential permit, stating it would not improve the United States’ energy security, would not “make a meaningful long-term contribution to [the] economy,” and would “undercut America’s ‘global leadership’ on climate change.” This was a major victory for climate change activists throughout the country. It showed the potential efficacy of climate change protests and civil disobedience, as it is unlikely that the government would have made such a determination without the public outcry. However, this victory was short lived, as President Trump granted approval for the Pipeline through an executive order in January of 2017, immediately after taking office. Still, despite the President’s actions after the fact, the protests were able to affect political change at the highest level of the executive branch. Although it is popular and effective, climate activists who wish to use civil disobedience still face a substantial problem. Their actions are, by definition, illegal. Therefore, individuals who plan on participating in such actions need to consider the risk of criminal prosecution. To avoid prosecution, the common law and, in some states, statutory law have provided defendants with a potential defense—the necessity defense. Put simply, “[t]he necessity defense asserts that breaking the law [is] justified in order to avert a greater harm that would occur as a result of the government policy the offender was protesting.” While it may be difficult to succeed on the assertion of a necessity defense in a climate change case, it has not stopped climate change advocates from attempting to assert the defense in the past. These activists—turned defendants—are not without help. The Climate Defense Project (“CDP”) is a group of attorneys committed to filling “a gap in the legal landscape by supporting front-line activists, pursuing climate impact litigation, and connecting attorneys with communities and campaigns.” One of the main avenues the group uses to support activists is facilitating climate activists’ use of the necessity defense. Inspired by the recent success of climate change defendants in asserting the necessity defense, and by the critical need for alternative avenues to combat climate change, this Note aims to provide guidance for climate change litigants who wish to use the necessity defense in climate change litigation. The goal of this Note is not to provide a thorough analysis of why the necessity defense is an appropriate mechanism to be used in climate change cases, as other scholars have already answered this question compellingly; rather, its aim is to provide climate change activists and litigants with important advice and considerations on how to use the necessity defense as effectively as possible. Since the burden to properly assert the necessity defense is extremely difficult to meet, especially in climate change cases, this Note hopes to play a role in assisting climate change litigants who attempt to use it.